Three new records of Didymosphaeriaceae from Southwest China - Yang, Hongde; Thiyagaraja, Vinodhini; Jayawardena, Ruvishika Shehali; Chomnunti, Putarak; Zhao, Qi; Hyde, Kevin David (Phytotaxa, 2025)
Several new and known species of Didymosphaeriaceae were reported from China in the past decade. In a survey of microfungi in the Southwest of China, three new Didymosphaeriaceae records were discovered based on a biphasic approach including multigene phylogenetic analyses (ITS, LSU, SSU, tef1-α and rpb2) and morphological characterizations. Tremateia chromolaenae is reported for the first time as a new host record on a dead stem of Buddleja asiatica. Montagnula guiyangensis is reported as new asexual morph and new host record from leaf lesions of Michelia wilsonii. This species is further reported as the second anamorphic state of the genus and notably, produced macro and microconidia. We also provided a new collection of M. aquatica, for the first time found in Motuo County, Xizang, China. Ecological metadata analysis based on ITS sequence data was conducted. The results were visualized using a Sankey diagram to illustrate the range of substrates, host associations, and geographic distributions, and a line chart to display monthly collection patterns. This study provides valuable insights into the distribution of Didymosphaeriaceae in China.